Implementación de un sistema de bombeo en serie para el abasto de agua al reservorio en la facultad de Ciencias Agropecuarias y Recursos Naturales de la Universidad Técnica de Cotopaxi. - Balseca Pazmiño, Orlando Raúl (2024)
Due to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the FDue to the requirement of the F3/, a fluid velocity of 0,8467 / and a discharge pressure of 550 KPa, directly affecting students and teachers in their daily activities. Therefore, the current state of the pumping system together with the water supply network was diagnosed, and an electrical design and combination of pumping equipment was developed to evaluate the water supply in order to ensure an adequate flow rate and stable pressure. For this purpose, some relevant calculations and measurements were performed obtaining the actual values of the pumping system with a flow rate of 0,45 ³/, a fluid velocity of 1.67 /, and a pressure of 723 KPa. The start, stop, and storage capacity of the tank were configured, the technical specifications of the motor were also analyzed based on the characteristic curves of the equipment and its connection and operation diagrams. To ensure correct operation of the system, its resistance, load losses, cavitation and general pressure losses were calculated. For the aforementioned tests, different measuring instruments such as flowmeter, sound level meter, manometer and vibrometer were used. It is concluded that the current state of the pumping system guarantees the study of the characteristic curves of the pumps, thus allowing an adequate connectivity to ensure the correct operation of conductors, pipes and accessories in accordance with the needs of the system.